Method for manufacturing negative electrode for secondary battery, negative electrode for secondary battery, and secondary battery
The method of coating and sintering a slurry of metal and silicon particles in an inert atmosphere addresses the challenges of manufacturing silicon-based negative electrodes for secondary batteries, enhancing capacity retention and eliminating the need for special equipment.
Patent Information
- Application Number
- JP2023168323
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-04-09
AI Technical Summary
Existing methods for manufacturing negative electrodes for secondary batteries using silicon as the active material require special equipment and are limited to atmospheric film formation, which is not suitable for electrodes prone to oxidation.
A method involving coating a slurry containing metal particles and silicon particles on a substrate, followed by sintering in an inert gas atmosphere to form a composite layer with a specific volume ratio of metal to silicon particles, which enhances bonding and capacity retention.
This method allows for the manufacture of negative electrodes with improved capacity retention and reduced reactivity, without the need for special equipment and in various atmospheres, thus addressing the limitations of previous technologies.
Smart Images

Figure 2025058408000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a method for producing a negative electrode for a secondary battery, a negative electrode for a secondary battery, and a secondary battery. [Background technology]
[0002] With the trend toward smaller and lighter electronic materials and the advancement of HEVs and EVs, there is a demand for batteries with large capacity, high-speed charge / discharge characteristics, high capacity retention, and greater safety. Among these, lithium-ion secondary batteries have been attracting attention as a promising battery due to their characteristics of higher voltage and higher energy density compared to other secondary batteries.
[0003] Currently, lithium-ion secondary batteries generally use LiCoO2 for the positive electrode and graphite for the negative electrode. However, although graphite negative electrodes have excellent reversibility in charge and discharge, their battery capacity has already reached a value close to the theoretical value of 372mAh / g, which corresponds to the intercalation compound LiC6, and in order to achieve even higher energy density, a negative electrode material with a battery capacity greater than that of graphite is required.
[0004] In recent years, the use of silicon as an anode active material has been investigated in order to further improve battery capacity. The theoretical capacity of silicon (4199mAh / g) is much larger than that of graphite (372mAh / g), so a significant improvement in battery capacity is expected.
[0005] However, when lithium ions are filled into silicon, its volume expands by about three times, resulting in a volume change of about 300% during charging and discharging. This causes the electrode structure to collapse, shortening the battery life and making it difficult to achieve a high capacity retention rate.
[0006] In response to the above-mentioned problems, a technology has been disclosed (Patent Document 1) in which a negative electrode active material layer is formed by adhering a negative electrode active material and a metal conductive material to the surface of a current collector using a deposition method that utilizes the impact bonding phenomenon (such as a powder jet deposition method (hereinafter referred to as PJD method)), and the porosity of the negative electrode active material layer is set to 10% or less, thereby reducing the surface area (reaction area) of the negative electrode active material layer and reducing reactivity, suppressing the decomposition reaction of the electrolyte and the resulting gas generation inside the battery, and improving cycle characteristics and swollenness characteristics.
[0007] However, the technology of Patent Document 1 forms a dense film, i.e., a negative electrode active material layer with a porosity of 10% or less, by a deposition method utilizing the impact bonding phenomenon such as the PJD method, and requires special equipment for carrying out the PJD method, etc., in addition to conventional battery manufacturing process equipment. Furthermore, deposition methods utilizing the impact bonding phenomenon such as the PJD method are limited to a film formation environment under air, and are not practical for application to the manufacture of electrodes that are easily oxidized in air. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2011-154901 A Summary of the Invention [Problem to be solved by the invention]
[0009] The present disclosure has been made in consideration of the above-described circumstances, and aims to provide a manufacturing method capable of manufacturing a secondary battery negative electrode using silicon as the negative electrode active material without adding special equipment to conventional battery manufacturing process equipment, and in which the film-forming atmosphere when forming the negative electrode active material layer is not limited to air. [Means for solving the problem]
[0010] In order to achieve the above object, the present disclosure provides the following means.
[0011] <Method of manufacturing negative electrode for secondary battery> [1] A method for producing a negative electrode for a secondary battery, comprising: applying a slurry containing metal particles, silicon particles, and a solvent to a substrate to form a coating film; and sintering the metal particles in the coating film to form a composite layer containing a sintered body of metal particles and silicon particles on the substrate. [2] The method for producing a negative electrode for a secondary battery according to [1], wherein the sintering is carried out at a temperature of 140° C. or higher and 300° C. or lower. [3] The method for producing a negative electrode for a secondary battery according to [1] or [2], wherein the sintering is carried out under an inert gas atmosphere. [4] The method for producing a negative electrode for a secondary battery according to any one of [1] to [3], further comprising drying the coating film at a temperature of 80° C. or higher and lower than 140° C. to form a sheet-shaped molded product on the substrate. [5] The method for producing a negative electrode for a secondary battery according to [4], wherein the sheet-like molded body has a thickness of 10 μm or more and 200 μm or less. [6] The method for producing a negative electrode for a secondary battery according to any one of [1] to [5], wherein the substrate is a current collector foil. [7] The method for producing a negative electrode for a secondary battery according to any one of [1] to [5], wherein the substrate is a release material. [8] The volume ratio of the metal particles is 50% by volume or more and 90% by volume or less with respect to the total volume of all raw materials constituting the composite layer; The method for producing a negative electrode for a secondary battery according to any one of [1] to [7], wherein a volume ratio of the silicon particles is 10 volume % or more and 50 volume % or less with respect to a total volume of all raw materials constituting the composite layer. [9] The method for producing a negative electrode for a secondary battery according to any one of [1] to [8], wherein the metal particles include nanometal particles.
[10] The method for producing a negative electrode for a secondary battery according to [9], wherein the metal nanoparticles are at least one selected from the group consisting of copper, nickel, cobalt, iron, zinc, aluminum, chromium, manganese, titanium, zirconium, molybdenum, tungsten, silver, indium and tin.
[11] The method for producing a negative electrode for a secondary battery according to [9] or
[10] , wherein the 50% particle size (d50) of the nanometal particles is 10 nm or more and 500 nm or less.
[12] The method for producing a negative electrode for a secondary battery according to any one of [1] to
[11] , wherein the silicon particles are at least one particle selected from the group consisting of simple silicon particles, silicon-based alloys, silicon monoxide composites, and silicon dioxide composites. <Negative electrode for secondary batteries>
[13] A negative electrode for a secondary battery, comprising a composite layer containing a sintered body of metal particles and silicon particles, wherein the volume ratio of the metal particles is 50 volume % or more and 90 volume % or less relative to the total volume of all raw materials constituting the composite layer, and the volume ratio of the silicon particles is 10 volume % or more and 50 volume % or less relative to the total volume of all raw materials constituting the composite layer.
[14] The negative electrode for a secondary battery according to
[13] , wherein the metal particles include nanometal particles. <Secondary battery>
[15] A secondary battery comprising the negative electrode for secondary batteries according to
[13] or
[14] and a positive electrode laminated together with a separator impregnated with an electrolytic solution therebetween. Effect of the Invention
[0012] According to the present disclosure, it is possible to provide a manufacturing method capable of manufacturing a secondary battery negative electrode using silicon as the negative electrode active material without adding special equipment to conventional battery manufacturing process equipment, and in which the film-forming atmosphere when forming the negative electrode active material layer is not limited to air. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a schematic cross-sectional view of a composite layer constituting a negative electrode for a secondary battery in one embodiment of the present disclosure. [Diagram 2] FIG. 1 is an explanatory diagram of a secondary battery according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, embodiments of the present disclosure will be described in detail. In the following description, the upper and lower limits of the numerical ranges can be combined in any manner.
[0015] [Negative electrode for secondary batteries] The negative electrode for a secondary battery in one embodiment may be formed by laminating a composite layer 2 on a current collector foil 1, which is a conductive member, as shown in FIG. In another embodiment, the negative electrode for a secondary battery may be formed only by the composite layer 2 without the current collector foil 1 .
[0016] <Composite layer> The composite layer 2 contains a sintered body of metal particles (A) and silicon particles (B) which are a negative electrode active material. The volume proportion of the metal particles (A) in the composite layer 2 may be 50 volume % or more and 90 volume % or less, 80 volume % or less, or 70 volume % or less, relative to the total volume of all raw materials constituting the composite layer 2. By making the volume ratio of the metal particles (A) 50% by volume or more, the bonds in the composite layer become strong, the battery can follow the volume change during charging and discharging, and the capacity retention rate is improved.
[0017] The volume proportion of the silicon particles (B) in the composite layer 2 may be 10 volume % or more and 50 volume % or less, 20 volume % or more, or 30 volume % or more, relative to the total volume of all raw materials constituting the composite layer 2. By setting the volume ratio of the silicon particles (B) to 10 volume % or more, the capacity and charge / discharge efficiency are improved.
[0018] [Method of manufacturing negative electrode for secondary battery] A method for producing a negative electrode for a secondary battery in one embodiment includes coating a substrate with a slurry containing metal particles (A), silicon particles (B), and a solvent to form a coating film, and sintering the metal particles in the coating film to form a composite layer 2 containing a sintered body of metal particles (A) and silicon particles (B) on the substrate. In the composite layer 2 having the above-mentioned structure, the metal particles (A) have three-dimensional metallic bonds around the silicon particles (B), which makes it difficult for silicon to separate. It is also assumed that the high capacity retention rate is achieved because the composite layer is less likely to crack even if volume changes occur during charging and discharging.
[0019] <Metal particles (A)> The metal particles (A) may include at least one of nano-metal particles (A1) and micron-metal particles (A2).
[0020] The metal particles (A) are not particularly limited, and may be particles made of a simple metal element such as copper, nickel, cobalt, iron, zinc, aluminum, chromium, manganese, titanium, zirconium, molybdenum, tungsten, silver, indium, or tin.
[0021] The shape of the metal particles (A) is not particularly limited, and may be, for example, flake-like or spherical.
[0022] The tap density (TD) of the metal particles (A) is 2.0 g / cm 3 More than 7.0g / cm 3 It may be the following.
[0023] <Nano metal particles (A1)> The 50% particle size (d50) of the nano metal particles (A1) may be 10 nm or more and 500 nm or less. The 50% particle size (d50) may be 20 nm or more and 400 nm or less. When the 50% particle size is in the above range, the sinterability of the particles is improved, and a composite layer can be formed with a small amount of metal particles (A). When the average particle size is 10 nm or more, the particles become stable, and when it is 500 nm or less, sufficient sinterability is obtained. In this specification, the 50% particle size (d50) is a volume-based median size measured by laser diffraction / scattering particle size distribution measurement.
[0024] <Micron metal particles (A2)> The 50% particle size (d50) of the micron metal particles (A2) may be 2 μm or more and 20 μm or less. The 50% particle size (d50) may be 2.5 μm or more and 15 μm or less. When the 50% particle size is in the above range, suitable sintering properties are obtained and sufficient strength of the composite layer is obtained. In addition, suitable thixotropy is obtained and coating properties of the slurry are improved.
[0025] <Volume ratio of nano metal particles (A1) and micron metal particles (A2)> The volume ratio of the metal nanoparticles (A1) to the metal particles (A) may be 20 volume % or more and 100 volume % or less relative to the total volume of the raw material metal particles (A). The volume ratio of the micron metal particles (A2) to the metal particles (A) may be 0 volume % or more and 80 volume % or less with respect to the total volume of the raw material metal particles (A). The total volume ratio of the nanometal particles (A1) and the micron metal particles (A2) in the metal particles (A) may be 80 volume % or more and 100 volume % or less based on the total volume of the raw material metal particles (A).
[0026] <Silicon particles (B)>
[0027] By using silicon particles (B) as the active material, the battery capacity is increased compared to the case where carbon is used. When lithium ions are filled into silicon particles (B), the volume expands to about three times, but in the secondary battery negative electrode of the present disclosure, the metal particles (A) have three-dimensional metallic bonds around the silicon particles (B), making it difficult for silicon to separate. It is also presumed that the high capacity retention rate is achieved because cracks are less likely to occur in the composite layer even if volume changes occur during charging and discharging. Examples of the silicon particles (B) include particles of silicon particles alone, silicon alloys, silicon monoxide composites, silicon dioxide composites, etc., and the shape of the particles may be any shape, such as granular, spherical, plate-like, scaly, needle-like, etc. Here, the silicon particles alone are a higher-level concept of silicon monoxide composites, and refer to crystalline or amorphous silicon having a purity of 95% by mass or more. Here, the silicon dioxide composite refers to a composite in which two or more compounds containing silicon dioxide are integrated together, and examples thereof include carbon-coated silicon dioxide. From the viewpoint of battery capacity, the silicon monoxide composite may be spherical in shape. The silicon monoxide composite means crystalline or amorphous silicon monoxide, and may be doped with lithium or coated with a carbon film.
[0028] The 50% particle size (d50) of the silicon particles (B) may be 10 μm or less, or 8 μm or less. Although there is no particular lower limit, from the viewpoint of workability, it may be 0.08 μm or more, 0.1 μm or more, or 1 μm or more. By setting the 50% particle size (d50) of the silicon particles (B) to 10 μm or less, deterioration of the composite layer and a decrease in capacity retention rate caused by the volume expansion of the silicon particles (B) can be avoided.
[0029] <Other ingredients> The composite layer may contain, in addition to the metal particles (A) and the silicon particles (B), a binder, a thickener, a conductive assistant, a coupling agent, a surfactant, and the like, as necessary.
[0030] Examples of the binder include carboxymethyl cellulose, polyvinylidene fluoride resin, polytetrafluoroethylene, styrene-butadiene copolymer, polyimide resin, polyamide resin, polyvinyl alcohol, polyvinyl butyral, polyacrylic acid or an alkali salt thereof, polyamic acid, etc. These may be modified by surface modification, etc.
[0031] The ratio of the binder may be 0.5 to 10.0 parts by mass, or 1.0 to 8.0 parts by mass, based on the total materials constituting the composite layer. By setting the ratio of the binder to 0.5 parts by mass or more, sufficient binding force between the negative electrode materials and between the negative electrode material and the current collector can be obtained, and high strength of the electrode can be obtained. By setting the ratio to 10.0 parts by mass or less, the reduction in battery capacity and the capacity retention rate are improved due to the improvement of the resistance value.
[0032] As the conductive assistant, for example, acetylene black, ketjen black, conductive resin, conductive fiber, flat graphite (graphene) having a particle size of 5 μm or less, or the like, which are generally known for use in secondary batteries, may be used.
[0033] The total volume percent of the metal particles (A) and the silicon particles (B) in the composite layer may be 90 volume percent or more, 93 volume percent or more, or 95 volume percent or more.
[0034] <Preparation of slurry> The metal particles (A) and silicon particles (B) may be mixed in a solvent to prepare a slurry.
[0035] The solids content of the slurry may be 60% by mass or more and 95% by mass or less, based on the total mass of the slurry. In the present disclosure, the solid content means components other than the solvent or dispersion medium in the slurry. The total content of the metal particles (A) and the silicon particles (B) in the solid content may be 80 to 100 mass %, may be 90 to 100 mass %, or may be 100 mass %.
[0036] The method for mixing the slurry may be either a dry method or a wet method, and examples thereof include a rotary ball mill, a planetary ball mill, a disperser, a homogenizer, and the like.
[0037] The solvent is not particularly limited as long as it is a material that can be mixed uniformly, and examples thereof include water, alcohols such as methanol and ethanol, N-methyl-2-pyrrolidone, acetonitrile, etc. These may be modified by surface modification or the like.
[0038] <Slurry coating> The substrate to which the slurry is applied may be a current collector foil or a release material.
[0039] The current collector foil may be made of any of the materials conventionally used for this purpose, such as copper, copper alloy, stainless steel, nickel, titanium, carbon, etc. The current collector foil is usually in the form of a sheet, and may have an uneven surface, a net, a punched metal, or the like.
[0040] The release material may be a release film in which the surface of a PET film is coated with silicone to impart releasability.
[0041] The method for applying the slurry is not particularly limited, and may be a method of continuous application by roll-to-roll, a method of application in a sheet-by-sheet manner, or the like. As the coating device, for example, a die coater, a multi-layer die coater, a gravure coater, a comma coater, a reverse roll coater, or a doctor blade coater is used.
[0042] <Drying of the coating> The coating film formed on the substrate by coating the slurry may be dried at 80° C. or higher and lower than 140° C. to form a sheet-like molded product on the substrate.
[0043] The thickness of the sheet-like molded body may be 10 μm or more and 200 μm or less, 150 μm or less, 100 μm or less, 10 μm or more and 150 μm or less, or 10 μm or more and 100 μm or less. The film thickness may be adjusted by changing the coating thickness of the slurry.
[0044] <Firing of coating film or sheet-like molded body> The coating film formed on the substrate by coating the slurry, or the sheet-like molded body after drying, may be fired at 140°C or higher and 300°C or lower to form a composite layer 2 containing a sintered body of metal particles (A) and silicon particles (B) on the substrate. The baking temperature may be 140° C. or more and 300° C. or less. The baking temperature may be 170° C. or more and 250° C. or less.
[0045] The firing atmosphere may be an inert gas atmosphere. The firing atmosphere may be a nitrogen atmosphere or an argon atmosphere. By firing in an inert atmosphere, deterioration of battery characteristics due to oxidation of the electrode can be reduced.
[0046] The calcination may be carried out under pressure or without pressure.
[0047] When the metal particles (A) contain less than 20% by volume of nanometal particles (A1), the metal particles (A) may be fired under pressure in order to sinter them at the firing temperature (i.e., low temperature conditions). When the metal particles (A) contain 20% by volume or more of the metal nanoparticles (A1), sintering without pressure is possible at the above-mentioned firing temperature, and firing may be performed without pressure.
[0048] When the metal particles (A) contain nano metal particles (A1), the composite layer 2 containing the sintered body of the metal particles (A) and the silicon particles (B) can contain minute voids (C). These minute voids (C) relieve the stress in the composite layer caused by the volumetric change of silicon during charging and discharging, so that the composite layer is less likely to crack even if a volumetric change occurs due to charging and discharging.
[0049] [Secondary battery and its manufacturing method] 2, the secondary battery in one embodiment is composed of a secondary battery negative electrode 3, a secondary battery positive electrode 4, an electrolyte 5, and a separator 6, and absorbs and releases lithium ions 7 during charging and discharging. The secondary battery negative electrode and the positive electrode may be laminated via a separator impregnated with an electrolytic solution.
[0050] <Positive electrodes for secondary batteries> The positive electrode material may be a lithium-cobalt composite oxide having a basic composition represented by LiCoO2, a lithium-nickel composite oxide represented by LiNiO2, a lithium-manganese composite oxide represented by LiMnO2 or LiMn2O4, or a lithium transition metal composite oxide such as manganese dioxide, or a mixture of these composite oxides. 0.33 Mn 0.33 Co 0.33 It may be O2 or the like.
[0051] The positive electrode may be fabricated by mixing these positive electrode materials with a binder, forming a slurry in a suitable solvent, and applying the slurry to a current collector and drying it.
[0052] The slurry may contain a conductive assistant generally known for use in secondary batteries, such as acetylene black, ketjen black, conductive resin, conductive fiber, flat graphite (graphene) having a particle size of 5 μm or less, etc. If desired, a binder may also be contained. As the binder, a binder well known for this purpose, such as one exemplified as one used for producing a negative electrode, may be used.
[0053] The positive electrode current collector may be made of aluminum, titanium, zirconium, hafnium, niobium, tantalum, or an alloy thereof such as stainless steel. At least one selected from the group consisting of aluminum, titanium, tantalum, and alloys thereof may be used, or aluminum or an alloy thereof may be used.
[0054] The positive electrode may be produced by a known method, for example, a method exemplified as a method for producing a negative electrode.
[0055] <Electrolytes> As the electrolyte, a known electrolytic solution, a room temperature molten salt (ionic liquid), an organic or inorganic solid electrolyte, or the like may be used.
[0056] An electrolyte having a lithium salt dissolved therein may be used as the electrolyte for the secondary battery. A flame-retardant electrolyte dissolving agent may be added to impart flame retardancy to the electrolyte. A plasticizer may be added to reduce the viscosity of the electrolyte. Any known lithium salt may be used.
[0057] <separator> A separator may be used to reduce short circuits between the positive and negative electrodes. The separator may be made of any known electrochemically stable material. Examples of the separator include a polyethylene separator, a polypropylene separator, a cellulose separator, a nonwoven fabric, an inorganic separator, a glass filter, and the like. When the electrolyte contains a polymer, the electrolyte may also function as a separator, in which case a separate separator is not necessary. EXAMPLES
[0058] Next, specific examples of the present disclosure will be described, but the present disclosure is not limited to these examples.
[0059] <Raw material for negative electrode> The raw materials shown in Table 1 were used as the negative electrode raw materials.
[0060] [Table 1]
[0061] <Preparation of negative electrode sheet for secondary battery> Each raw material described as "negative electrode raw material" in Table 2 was placed in a stirring vessel. In Table 2, blanks indicate no blending. The stirring vessel containing the raw materials was set in a planetary centrifugal mixer (Thinky Corporation, model number: ARV-310) and mixed for 6 minutes at a rotation speed of 2,000 rpm in air. Next, using Filmix (registered trademark), the mixture was mixed for 6 minutes at a peripheral speed of 35 m / sec to prepare a negative electrode-forming slurry. Using a μ-coat 350 manufactured by Yasui Seiki Co., Ltd., the negative electrode forming slurry was applied onto one surface of a copper foil by gravure coating, and then dried to form a sheet-like molded product having a thickness of 75 μm. The copper foil was placed in a drying furnace and heated at 85° C. for 10 minutes to volatilize the solvent from the sheet-shaped molded body. The drying furnace was then filled with nitrogen gas and the sheet was fired at 200° C. for 1 hour to prepare a negative electrode sheet for a secondary battery.
[0062] <Preparation of positive electrode sheet for secondary battery> The raw materials shown in Table 2 as "raw materials for positive electrode" were mixed at 25° C. using a planetary mixer (Thinky Corporation, model number: ARV-310) to prepare a slurry for forming a positive electrode. The amounts of each ingredient are as shown in Table 2. Using a μ-Coat 350 manufactured by Yasui Seiki Co., Ltd., the slurry for forming the positive electrode was supplied onto one side of a current collector foil SUS444 H BD (manufactured by Nippon Steel Chemical & Material Co., Ltd.) and coated by gravure coating. After coating, the slurry was dried under conditions of a temperature of 100°C and a speed of 0.2 m / min to prepare a positive electrode sheet for a secondary battery having a thickness of 60 μm.
[0063] [Table 2]
[0064] <Creating secondary batteries> The negative electrode sheet for secondary batteries and the positive electrode sheet for secondary batteries were roll-pressed (pressure: 1.5 MPa) using a 250 mmφ roll press equipped with a load cell, punched out into circular shapes with a diameter of 12.5 mm, and vacuum-dried at 110° C. for 2 hours to obtain negative and positive electrodes for evaluation. The negative electrode and the positive electrode were stacked with a separator (S703-1, manufactured by Sumitomo Chemical Co., Ltd.) impregnated with an electrolyte interposed therebetween to prepare a secondary battery for charge / discharge tests. The electrolyte was a mixture of ethylene carbonate and diethylene carbonate (volume ratio 1:1) in which lithium hexafluorophosphate was dissolved at a concentration of 1 mole / liter.
[0065] <Evaluation method: negative electrode> The "active material capacity" of the produced negative electrode sheet for secondary batteries was measured by the following method. The measurement results are shown in Table 3. 《Active material capacity (mAh / g)》 A half cell composed of the negative electrode sheet for secondary batteries and Li foil was charged at a constant current of 0.5 mA until the circuit voltage reached 0 mV, and then switched to constant voltage charging when the circuit voltage reached 0 mV, and continued charging until the current value reached 0.05 mA. After that, it was paused for 30 minutes. Next, a constant current discharge was performed at a current of 0.5 mA until the circuit voltage reached 3.0 V, and then switched to constant voltage discharge when the circuit voltage reached 3.0 V, and continued discharging until the current value reached 0.05 mA. This charge / discharge cycle was repeated for two cycles, and the active material capacity was calculated using the following formula: In this test, the process of absorbing and extracting lithium into the active material was defined as charge, and the process of absorbing and extracting lithium was defined as discharge. Active material capacity (mAh / g) = Discharge capacity in the second cycle / Mass of negative electrode active material
[0066] <Evaluation method - secondary battery> The charge / discharge efficiency (Coulomb efficiency) of the secondary batteries thus produced was measured by the following method. The measurement results are shown in Table 3. 《Charge / discharge efficiency》 Charge and discharge tests were carried out on the secondary batteries of Examples 1 to 9, and the charge and discharge efficiency was calculated. Charging was carried out under the conditions of a cut-off voltage of 3.7 V, 0.05 C, and 25° C. Discharging was carried out under the conditions of a cut-off voltage of 1.9 V, 0.05 C, and 25° C. The test started with charging, and the ratio (%) of the discharge capacity to the charge capacity was calculated as the charge and discharge efficiency.
[0067] [Table 3] [Industrial Applicability]
[0068] The negative electrode for secondary batteries of the present disclosure is suitable for use as a negative electrode for liquid lithium ion secondary batteries (LIBs). [Explanation of symbols]
[0069] 1 Current collecting foil A Metal particles A1 Nano metal particles A2 micron metal particles B Silicon particles 2 composite layers C void 3 Negative electrode for secondary batteries 4. Positive electrodes for secondary batteries 5 Electrolytes 6 Separator 7. Lithium-ion
Claims
1. Coating a substrate with a slurry containing metal particles, silicon particles, and a solvent to form a coating film; sintering the metal particles in the coating to form a composite layer containing a sintered body of metal particles and silicon particles on the substrate.
2. The method for producing a negative electrode for a secondary battery according to claim 1 , wherein the sintering is carried out at a temperature of 140° C. or more and 300° C. or less.
3. The method for producing a negative electrode for a secondary battery according to claim 1 or 2, wherein the sintering is carried out in an inert gas atmosphere.
4. The method for producing a negative electrode for a secondary battery according to claim 1 or 2, further comprising drying the coating film at a temperature of 80° C. or higher and lower than 140° C. to form a sheet-like molded body on the substrate.
5. The method for producing a negative electrode for a secondary battery according to claim 4 , wherein the sheet-like molded body has a thickness of 10 μm or more and 200 μm or less.
6. The method for producing a negative electrode for a secondary battery according to claim 1 , wherein the substrate is a current collector foil.
7. The method for producing a negative electrode for a secondary battery according to claim 1 or 2, wherein the substrate is a release material.
8. The volume ratio of the metal particles is 50% by volume or more and 90% by volume or less with respect to the total volume of all raw materials constituting the composite layer, 3 . The method for producing a negative electrode for a secondary battery according to claim 1 , wherein a volume ratio of the silicon particles is 10% by volume or more and 50% by volume or less with respect to a total volume of all raw materials constituting the composite layer.
9. The method for producing a negative electrode for a secondary battery according to claim 1 , wherein the metal particles include nanometal particles.
10. The method for producing a negative electrode for a secondary battery according to claim 9, wherein the nanometal particles are at least one selected from the group consisting of copper, nickel, cobalt, iron, zinc, aluminum, chromium, manganese, titanium, zirconium, molybdenum, tungsten, silver, indium and tin.
11. The method for producing a negative electrode for a secondary battery according to claim 9, wherein the 50% particle size (d50) of the nanometal particles is 10 nm or more and 500 nm or less.
12. 3. The method for producing a negative electrode for a secondary battery according to claim 1, wherein the silicon particles are at least one particle selected from the group consisting of simple silicon particles, silicon-based alloys, silicon monoxide composites, and silicon dioxide composites.
13. A composite layer including a sintered body of metal particles and silicon particles, The volume ratio of the metal particles is 50% by volume or more and 90% by volume or less with respect to the total volume of all raw materials constituting the composite layer, a volume ratio of the silicon particles to the total volume of all raw materials constituting the composite layer is 10 volume % or more and 50 volume % or less.
14. The negative electrode for a secondary battery according to claim 13 , wherein the metal particles include nanometal particles.
15. A secondary battery comprising the negative electrode for secondary batteries according to claim 13 or 14, a positive electrode, and a separator impregnated with an electrolytic solution therebetween.
Citation Information
Patent Citations
Lithium ion secondary battery and negative electrode for the same
JP2011154901A